Excited states in 163,164Ho populated through incomplete fusion - Hojman, Daniel Leonardo; Cardona, Maria Angelica; Bazzacco, D.; Blasi, N.; Davidson, Jorge; Davidson, Miguel; Debray, Mario Ernesto; Kreiner, Andres Juan; Lenzi, S. M.; Lo Bianco, G.; Napoli, D. R.; Rossi Alvarez, C. (Springer, 2004)
Fil: Hojman, Daniel Leonardo. Comisión Nacional de Energía Atómica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina